2019
DOI: 10.2147/cmar.s207257
|View full text |Cite
|
Sign up to set email alerts
|

<p>Eupatilin inhibits glioma proliferation, migration, and invasion by arresting cell cycle at G1/S phase and disrupting the cytoskeletal structure</p>

Abstract: Purpose: Eupatilin is a pharmacologically active flavonoid extracted from Asteraceae argyi that has been identified as having antitumor effects. Gliomas are the most common intracranial malignant tumors and are associated with high mortality and a poor postoperative prognosis. There are few studies on the therapeutic effects of eupatilin on glioma. Therefore, we explored the efficacy and the underlying molecular mechanism of eupatilin on glioma. Methods: The effect of eupatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 42 publications
(43 reference statements)
1
21
0
Order By: Relevance
“…Eupatilin also activates the apoptotic pathway mediated by the cleavage of caspase-3 in gastric cancer cells, similar to the results verified in ovarian cancer cells in this study [23]. Moreover, cell cycle arrest is one of the routes of eupatilin-induced anticancer effects in gastric cancer and glioma, as demonstrated in ovarian cancer cells [24,25]. Eupatilin also triggered apoptosis by elevating p53 and p21 in agreement with the Bax, Bcl-2, and Parp regulations in human gastric cancer (AGS) cells [23].…”
Section: Discussionsupporting
confidence: 88%
“…Eupatilin also activates the apoptotic pathway mediated by the cleavage of caspase-3 in gastric cancer cells, similar to the results verified in ovarian cancer cells in this study [23]. Moreover, cell cycle arrest is one of the routes of eupatilin-induced anticancer effects in gastric cancer and glioma, as demonstrated in ovarian cancer cells [24,25]. Eupatilin also triggered apoptosis by elevating p53 and p21 in agreement with the Bax, Bcl-2, and Parp regulations in human gastric cancer (AGS) cells [23].…”
Section: Discussionsupporting
confidence: 88%
“…For instance, eupatilin inhibits endometrial cancer cell growth by inducing G2/M phase cell cycle arrest and regulating ERK and AKT phosphorylation [13]. Eupatilin also suppresses proliferation, migration, and invasion, and it induces cell cycle arrest at the G1/S phase in glioma cells [11,29]. In esophageal cancer cells, eupatilin suppresses cell growth by inhibiting AKT and ERK phosphorylation, as well as by inducing G1 phase arrest [10].…”
Section: Discussionmentioning
confidence: 99%
“…One study screened a library of 273 kinase inhibitors and identified thiazovivin (a pyrimidine-based non-selective ROCK inhibitor) as a significant hit (63). It is also interesting to note that the plant flavanoid, eupatilin, which was highlighted as a potential therapeutic for CEP290 -related retinal dystrophy (11) and has been used to treat the Rpgrip1l -/- mouse (64), has an indirect effect on actin cytoskeleton remodelling that is mediated by CEP290 (65). Several other screens have identified other biological targets for the restoration of cilia, for example a screen to identify drugs that restore cilia expression in cancer cells identified 118 compounds, many of which affect levels of cAMP, calcium or other ions (66).…”
Section: Discussionmentioning
confidence: 99%